Handbook of vehicle suspension control systems - Gao, Huijun; Li, Ping; Liu, Honghai (Institution of Engineering and Technology, 2013)
This book presents recent control theory and applications for vehicle suspension systems. From the systematic point of view, a vehicle control system is composed of key components such as modeling, sensing, controller, and actuator. It is not our intention to cover all the technical details of recent control-related contributions in the context of vehicle suspensions, but priority has been given to recently reported novel control methods and key challenges in the past decades. This book consists of 13 self-contained chapters covering recent theoretical developments and applications in active suspension systems.